2013
DOI: 10.1128/mbio.00540-13
|View full text |Cite
|
Sign up to set email alerts
|

The Activity and Specificity of the Outer Membrane Protein Chaperone SurA Are Modulated by a Proline Isomerase Domain

Abstract: SurA is a component of the periplasmic chaperone network that plays a central role in biogenesis of integral outer membrane β-barrel proteins (OMPs) in Escherichia coli. Although SurA contains two well-conserved proline isomerase (PPIase) domains, the contribution of these domains to SurA function is unclear. In the present work, we show that defects in OMP assembly caused by mutation of the β-barrel assembly factors BamA or BamB can be corrected by gain-of-function mutations in SurA that map to the first PPIa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 41 publications
3
29
0
Order By: Relevance
“…Indeed, a role for the SurA P1 domain in vivo was revealed only when surA10 was isolated in a background defective for BAM complex function (27). We thus suspected that a properly functioning BAM complex might mask any phenotype imposed by the deletion of the SurA parvulin domains.…”
Section: Deletion Of the Second Parvulin Domain Results In Inhibition Ofmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, a role for the SurA P1 domain in vivo was revealed only when surA10 was isolated in a background defective for BAM complex function (27). We thus suspected that a properly functioning BAM complex might mask any phenotype imposed by the deletion of the SurA parvulin domains.…”
Section: Deletion Of the Second Parvulin Domain Results In Inhibition Ofmentioning
confidence: 99%
“…It had been previously demonstrated that many of the OMP assembly factors, including chaperones and BAM complex members, function in overlapping and redundant pathways (4,14,27). Indeed, a role for the SurA P1 domain in vivo was revealed only when surA10 was isolated in a background defective for BAM complex function (27).…”
Section: Deletion Of the Second Parvulin Domain Results In Inhibition Ofmentioning
confidence: 99%
See 3 more Smart Citations